Assessing the benefits of serious games to support sustainable decision-making for transboundary watershed governance. Issue 4 (2nd October 2018) - Furber, Alison; Medema, Wietske; Adamowski, Jan
Abstract : The overarching objective of this paper is to consider the ways that serious games could be developed in the future to maximise potential benefits in the context of governance of complex transboundary water systems. A focus is placed on the use of serious games for decision-making; as such the use of serious games for other purposes (e.g. games with a solely educational purpose), while interesting and useful, is outside the scope of this work. The Upper St Lawrence was used as a case study of a transboundary watershed to enable specific examples of the potential uses of serious games to be drawn. A review of the serious games and decision-making literature was undertaken to derive a theory framework for the way serious games might be able to support decision-making in different contexts. Following this, exploratory interviews were conducted with water resource managers across the St Lawrence region to establish whether a serious game might be useful in this particular context. Three decision-making contexts were identified in which serious games might be a useful tool: decision-making involving complex systems or significant uncertainty, decision-making involving multiple stakeholders with divergent perspectives and decision-making under time constraints. It was found that several contextual factors make the St Lawrence region a potentially viable candidate for the development of a serious game to support decision-making.